2009
DOI: 10.1186/1476-9255-6-28
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus casei modulates the inflammation-coagulation interaction in a pneumococcal pneumonia experimental model

Abstract: Background: We have previously demonstrated that Lactobacillus casei CRL 431 administration improved the resistance to pneumococcal infection in a mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…Indeed, it has been reported that some types for probiotic bacteria influence markers of coagulation in a beneficial manner (38). However, we found no effect of Cardi04 yogurt on any of the key markers of coagulation measured in this study.…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed, it has been reported that some types for probiotic bacteria influence markers of coagulation in a beneficial manner (38). However, we found no effect of Cardi04 yogurt on any of the key markers of coagulation measured in this study.…”
Section: Discussioncontrasting
confidence: 56%
“…This suggests that the enhancement of plasmin activity by lactobacilli remains local and could function, e.g., to contribute to the dissolution of fibrin clots or thrombi over a wound site. Along these lines, it was reported previously that the treatment of mice suffering from pneumococcal pneumonia with Lactobacillus casei lowers the amount of fibrin(ogen) deposits in the lung (1,22), and the potential of synbiotics to reduce procoagulatory factors has been recognized (8). The mechanisms of these in vivo effects obviously are complex, but our results encourage further studies of the role and the mechanisms of the modulation of the fibrinolysis/coagulation cascades by commensal bacteria.…”
Section: Discussionmentioning
confidence: 73%
“…Even though it is beneficial in most cases, it has also been associated with endocarditis (24), pulmonary abscess, and pleuritis (25). Lactobacillus casei was found to have a protective role in the lung of a mouse model during Streptococcus pneumoniae infection (26). In patient CF8, the presence of Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%